Pelatihan Public Speaking Bagi Mahasiswa Perguruan Tinggi Advent Surya Nusantara, Pematang Siantar - Nilamsari, Natalina; Sitorus, Kristina Berliana (Jurnal Pustaka Dianmas, 2023)
Public speaking is a soft skill of communication science, which provides a primary guidance to be skilled speaking in front of audiences. For students of major in accounting at Perguruan Tinggi Advent Surya Nusantara (PTASN) in Pematang Siantar North Sumatera, this training provides benefits for self-development as well as preparation to impenetrate the realm of workplce or  profession. This was the reason for carrying out this community service activity, attended by 45 students. Activities in the form of training held on the PTASN campus for one day. During the training, participants were given material on public speaking and practice and were evaluated by the facilitator. Implementation of the program starts from the early observation, orientation, provision of learning material, practice and evaluation. The results of the training were considered good based on the participants' enthusiasm and their confidence’s when practice of public speaking .